2020
DOI: 10.1038/s41477-020-0656-9
|View full text |Cite
|
Sign up to set email alerts
|

Organic management promotes natural pest control through altered plant resistance to insects

Abstract: rganic farming is characterized by management practices that promote soil biodiversity and beneficial ecological interactions to offset the need for synthetic inputs such as inorganic fertilizers and biocides. Pest and nutrient management in organic agriculture is largely accomplished through various diversification methods, including cover crops, crop rotations, trap crops and promotion of active soil microbial communities [1][2][3][4][5] . Although organic agriculture is often thought to be less productive i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 62 publications
1
57
0
3
Order By: Relevance
“…This finding is in line with our previous work, which has suggested that successional shifts in soil microbiomes are an important factor driving increases in the herbivore resistance of a wild plant ( Howard et al., 2020 ), yet the underlying mechanisms for this microbe-mediated resistance are still unresolved. However, it is becoming clearer that various early successional forbs and grasses ( Pineda et al., 2020 ), as well as organic management practices ( Blundell et al., 2020 ), can condition soil to promote herbivore resistance. Thus, in addition to providing related ecosystem services as habitat for natural enemies of pests ( Denys and Tscharntke, 2002 ), fallow land may be worth investigating as sources of beneficial soil microbiomes that are adapted to local edaphic conditions, not only potentially improving their establishment and efficacy ( Hawkes and Connor, 2017 ), but also reducing the non-target risks of introducing non-native microbes ( Hart et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is in line with our previous work, which has suggested that successional shifts in soil microbiomes are an important factor driving increases in the herbivore resistance of a wild plant ( Howard et al., 2020 ), yet the underlying mechanisms for this microbe-mediated resistance are still unresolved. However, it is becoming clearer that various early successional forbs and grasses ( Pineda et al., 2020 ), as well as organic management practices ( Blundell et al., 2020 ), can condition soil to promote herbivore resistance. Thus, in addition to providing related ecosystem services as habitat for natural enemies of pests ( Denys and Tscharntke, 2002 ), fallow land may be worth investigating as sources of beneficial soil microbiomes that are adapted to local edaphic conditions, not only potentially improving their establishment and efficacy ( Hawkes and Connor, 2017 ), but also reducing the non-target risks of introducing non-native microbes ( Hart et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…that induced systemic pathogen susceptibility increased tomato plants' resistance to T. ni, further indicating that the salicylic acid-jasmonic acid trade-off may play an important role in mediating rhizosphere microbial influence on insect herbivory (Haney et al, 2018). Another recent study (Blundell et al, 2020) implicated salicylic acid as an important mediator of soil microbe-influenced resistance to a hemipteran herbivore (which generally tend to be more strongly affected by salicylic acid-versus jasmonic acid-mediated defenses), further emphasizing the potential importance of rhizosphere microbes affecting plant-insect interactions through altering phytohormonal signaling. Thus, changes in the functional composition of soil microbial communities, including the abundance of pathogens-which are expected to shift over fallow succession (Hannula et al, 2017)-could affect herbivore resistance through altering plant defense responses.…”
Section: Proportion Of Choicesmentioning
confidence: 92%
See 1 more Smart Citation
“…Plant-insect-microbe interactions occurring in the rhizosphere can have dramatic effects across trophic levels, above and below ground, and can shape plant, herbivore, and microbial communities [152]. Beneficial microbial communities can provide plants with increased pest resistance [153]. Plants release a suite of chemicals from roots upon insect damage to which specific microbes respond.…”
Section: Enhancing Plant Health-promoting Microbesmentioning
confidence: 99%
“…In the case of maize, benzoxazinoids have been shown to alter the rhizosphere microbiome, providing potential benefits to maize in the form of pest suppression in following generations [155]. Organic practices that promote soil health can also alter plant resistance to aboveground pest pressure [153]. However, there has been little work to investigate how these rhizosphere interactions affect western corn rootworm.…”
Section: Enhancing Plant Health-promoting Microbesmentioning
confidence: 99%